The polyanions heparin and suramin impede binding of free adenine to a DNA glycosylase from C. pseudotuberculosis - Eberle, Raphael J. [UNESP]; Coronado, Monika A. [UNESP]; Peinado, Rafaela S. [UNESP]; de Moraes, Fabio R. [UNESP]; Olivier, Danilo [UNESP]; Dreyer, Thiago [UNESP]; de Oliveira Lopes, Debora; da Luz, Brenda Silva Rosa; Azevedo, Vasco; Arni, Raghuvir K. [UNESP] (Elsevier, 2019)
Currently no effective treatment is available to combat infections caused by Corynebacterium pseudotuberculosis in livestock. Survival of this Gram-positive bacterium in rapidly-growing pathogens in hostile environments is strongly dependent on the existence of a robust DNA repair system to prevent DNA mutations and contribute to bacterial colonization and virulence. The adenine/guanine-specific DNA glycosylase (MutY) is evolutionarily conserved and has been well characterized due to its central role in the prevention of mutagenesis and DNA repair. The aim of this study was the characterization of the target protein interaction with free adenine, suramin, and heparin, as well as the binding competition characterization between the molecules. The dissociation constant for free adenine interaction with Corynebacterium pseudotuberculosis MutY (Cp-MutY) was determined, 86 ± 2.5 μM. NMR competition experiments demonstrated, that the polyanions heparin and suramin compete with adenine for the protein active site. The determined dissociation constant for the heparin/Cp-MutY interaction was 5.9 ± 1.0 μM and for suramin was 16 ± 1.5 μM. Docking of both polyanions with Cp-MutY revealed a possible mode of interaction and indicates that these molecules can interfere with the protein interaction with damaged DNA or prevent the binding of the adenine base in the enzyme active site.
Keywords: Adenine; Competition; Corynebacterium pseudotuberculosis; MutY; Polyanions